2022
DOI: 10.1371/journal.pone.0263444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines and consensus statements for antenatal oral healthcare: An assessment of their methodological quality and content of recommendations

Abstract: Objectives To review the content of recommendations within antenatal oral healthcare guidance documents and appraise the quality of their methodology to inform areas of development, clinical practice, and research focus. Method A systematic search of five electronic databases, Google search engine, and databases from relevant professional and guideline development groups published in English, developed countries, and between 2010 and 2020 was undertaken to identify guidance documents related to antenatal ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(35 reference statements)
0
4
0
1
Order By: Relevance
“…The need to develop, adopt, adapt or contextualise guidelines on self-management support for resource-limited and high-burden TB-HIV coinfection settings may be more urgent in resource-limited settings since all of the existing guidelines were developed for high-income settings such as Australia, Canada, England and the United States of America. Previous reviews have reported similar dominance of high-income countries in developing guidelines [ 23 26 ]. Guideline development groups in resource-limited settings can utilise rigorous yet pragmatic approaches such as the GRADE Adolopment approach to produce context-relevant self-management support recommendations from available high-quality guidelines [ 21 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The need to develop, adopt, adapt or contextualise guidelines on self-management support for resource-limited and high-burden TB-HIV coinfection settings may be more urgent in resource-limited settings since all of the existing guidelines were developed for high-income settings such as Australia, Canada, England and the United States of America. Previous reviews have reported similar dominance of high-income countries in developing guidelines [ 23 26 ]. Guideline development groups in resource-limited settings can utilise rigorous yet pragmatic approaches such as the GRADE Adolopment approach to produce context-relevant self-management support recommendations from available high-quality guidelines [ 21 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have mapped recommendations and critically assessed the quality of existing guidelines on depression [ 23 , 24 ], emergency [ 25 ], oral [ 26 ], and prehospital care [ 27 ]. However, no existing reviews have searched and appraised TB-HIV related self-management support best practice guidelines and their recommendations to inform guideline adaptation, guide healthcare, promote education or inform policy.…”
Section: Introductionmentioning
confidence: 99%
“…Those with low and extremely low food security had poorer dental/oral health results than those with high food security [ 6 , 8 , 25 ]. Although the links between food security, socioeconomic position, nutrition practices, and dental health are complex, examining these linkages may provide the insight needed to build successful and lasting nutrition education programs, particularly for children and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Although the links between food security, socioeconomic position, nutrition practices, and dental health are complex, examining these linkages may provide the insight needed to build successful and lasting nutrition education programs, particularly for children and their parents. The evaluation of one intervention in a low-income setting allowed researchers to investigate the relationship between oral health concerns, income, food security, eating behaviors, and attitudes [ 8 , 25 ]. Concerns about overall health logically follow oral health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Com isso, complicações ou efeitos indesejáveis podem incorrer na saúde gestacional, levando à pré-eclâmpsia, diabetes mellitus gestacional e até ao nascimento prematuro ou baixo peso da criança. 2,3,6 Nesse sentido, no cenário da saúde pública brasileira, através das Diretrizes da PNSB, o Ministério da Saúde (MS) preconiza o atendimento odontológico no pré-natal como uma ação complementar, considerando as gestantes como um grupo prioritário na Estratégia Saúde da Família. Com ênfase na saúde pública, esse atendimento possibilita controlar possíveis variáveis que influenciam negativamente a evolução saudável da gestação.…”
Section: Introductionunclassified